Endoscopic anti-reflux valve for post-esophagectomy reflux: an animal study - Yanagimoto, Yoshitomo; Yamasaki, Makoto; Nagase, Hirotsugu; Kanemura, Takashi; Higashi, Shigeyoshi; Miyazaki, Yasuhiro; Makino, Tomoki; Takahashi, Tsuyoshi; Kurokawa, Yukinori; Miyata, Hiroshi; Takiguchi, Shuji; Mori, Masaki; Doki, Yuichiro; Nakajima, Kiyokazu (Endoscopy, 2016)
Background and study aims: Gastric reflux into the remnant esophagus after subtotal or partial esophagectomy is associated with impairment in patient quality of life. We evaluated the feasibility, safety, and potential effectiveness of a novel procedure using a new endoscopic suturing device to create an anti-reflux valve (funnel) in pigs after esophagectomy with gastric tube reconstruction.Methods: The endoscopic procedure was performed in four pigs using a semi-full-thickness endoscopic suturing system (OverStitch; Apollo Endosurgery, Austin, Texas, USA). The operating time, funnel height, ratio of the height of the funnel to the diameter of the gastric tube, and adverse events associated with the procedure were evaluated. The “reflux angle” was measured morphologically and functionally during a reflux induction test, using contrast medium or artificial gastric fluid, by tilting the operating table gradually from a head up to a head down position. Reflux angles before and after funnel creation were compared.Results: The procedure was successful in all four animals. The median operating time was 43 minutes, and the median funnel height was 17 mm (56.7 % of gastric tube diameter). There were no adverse events associated with the procedure. The reflux angle was lower after the procedure compared with before in both morphological and functional assessments in all four cases.Conclusions: Endoscopic anti-reflux funnel creation using OverStitch was feasible, safe, and potentially effective.